2010
DOI: 10.1080/00140130903067763
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress in submariners: The impact of isolated and confined work on psychological well-being

Abstract: This study aimed to identify work-related and personal factors associated with occupational stress in submariners. Work and well-being questionnaires were distributed to 219 male submariners (mean age 34 years), as part of a larger cohort study involving a stratified sample of 4951 Royal Navy (RN) personnel. The stress rate in submariners was 40%; significantly higher than the stress rate in the general RN, although once demographic factors were controlled for in a matched control sample, this difference was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…These results further corroborates Kirkcaldy et al's (1998) and Brasher et al's (2010) findings which found an inverse relation between the occupational stress and job ranks. Moreover, Brasher et al (2010) argued that increased status, autonomy, task variation and living accommodation inherent in superior rank reduces the stress levels of higher ranked personnel. As hypothesized, our results show statistically significant differences in occupational stressors based on designation level of soldiers, but the results offer support for only three occupational stressors.…”
Section: Designationmentioning
confidence: 99%
See 2 more Smart Citations
“…These results further corroborates Kirkcaldy et al's (1998) and Brasher et al's (2010) findings which found an inverse relation between the occupational stress and job ranks. Moreover, Brasher et al (2010) argued that increased status, autonomy, task variation and living accommodation inherent in superior rank reduces the stress levels of higher ranked personnel. As hypothesized, our results show statistically significant differences in occupational stressors based on designation level of soldiers, but the results offer support for only three occupational stressors.…”
Section: Designationmentioning
confidence: 99%
“…Brasher et al (2010) highlighted an inverse relation between the stress levels and the ranks of Royal Navy personnel in the United Kingdom, indicating lower stress levels among higher ranked employees. Pestonjee and Azeem (2001) identified higher level of role stress in lecturers compared with readers and professors, while Gillespie, Walsh, Winefield, Dua and Stough (2001) found moderate to high level of work stress among the academic staff than the general staff.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Andrew P. Smith, An update on stress, fatigue and wellbeing: implications for naval personnel Comparisons have been made between specific roles (e.g. submariners) and a stratified sample of naval personnel [40]. However, other research has considered quality of life and extended this to naval nurses [41] and naval families [42].…”
Section: Stress Fatigue and Wellbeing In The Navymentioning
confidence: 99%
“… 10 However, submariners are concurrently exposed to various environmental risk factors that can affect their health status, such as their confined work environment, physical inactivity, excessive caloric intake, circadian disruption and isolation from family during deployment. 11–13 A few studies evaluating the effects of these occupational risk factors on submariners’ health status have reported controversial findings. A Norwegian study revealed that submariners had increased risk of bladder cancer and non-melanoma skin cancer.…”
Section: Introductionmentioning
confidence: 99%